New and future developments in microbial biotechnology and bioengineering : trends of microbial biotechnology for sustainable agriculture and biomedicine systems.: trends of microbial biotechnology for sustainable agriculture and biomedicine systems. Diversity and functional perspectives / (2020) - Unknown
No abstract available